Influence of mycorrhizal fungi on growth and cadmium adsorption in sunflower (Helianthus annuus L.) - Cartaya-Rubio, Omar Enrique; Mujica-Perez, Yonaisy; Blanco-Valdes, Yaisys (Agronomía Mesoamericana, 2024)
Introduction. Heavy metals can accumulate in the soil and affect plant growth. The symbiosis established between plants and arbuscular mycorrhiza-forming fungi (AMF) improves the tolerance of plants to heavy metal toxicity, being considered an alternative for the management of plants grown in soils affected by heavy metals. Objective. To evaluate the effect of different arbuscular mycorrhizal-forming fungi on cadmium (Cd) adsorption and vegetative growth of sunflower (Helianthus annuus L.). Materials and methods. The research was carried out in the years 2021-2023, at the National Institute of Agricultural Sciences (INCA), San José de las Lajas, Mayabeque, Cuba. Sunflower seeds were inoculated with the strains INCAM-4 (Glomus cubense) and INCAM-11 (Rhizoglomus intraradices), at a rate of 45 spores/g, in a soil with high levels of Cd. After 60 days, the plant height, dry weight, chlorophyll content, percentage of mycorrhization and viability of fungal structures, and the effect of AMF on cadmium partitioning in sunflower plants were evaluated. Results. Sunflower plants showed a beneficial response to inoculation with strains of arbuscular mycorrhizal fungi, with a differentiated behavior between the strains and with the greatest effects obtained in growth, biomass production and in the phytoextraction process with the INCAM-11 strain, by increasing the concentration of metal in the plants to 8.01 mg kg-1 and an infection percentage of 60 % and a visual density of 5.01. Conclusions. Arbuscular mycorrhizae increased cadmium adsorption and vegetative growth of sunflower.